Legal Facets of the Practice of International Organizations - Blokker, Niels (The Pocket Books of The Hague Academy of International Law / Les livres de poche de l'Académie de droit international de La Haye, 2025)
The aim of this special course is to discuss a number of legal facets of the practice of international organizations. A first legal facet is "practice as a rule". Here, the notion of "established practice" will be analyzed. The second legal facet covered by this course is "practice as a power", discussing the power generating capacity of the practice of international organizations. The third legal facet concerns practice of international organizations as an interpretative device. The fourth and fifth legal facet will analyze how the International Court of Justice and the International Law Commission have dealt with the practice of international organizations in their work. Overall, the analysis of these legal facets demonstrates that the function of law in the practice of international organizations is to provide these organizations and their members with a flexible framework for shared sovereignty.